Mirafiori sud: la città fordista oltre la Fabbrica. Scenari e progetti per (la costruzione di) una nuova identità - de Filippi, Francesca; Vassallo, Ianira (Ri-Vista. Research for landscape architecture, 2016)
Mirafiori is a model city now passed, disappeared. It’s one of the most significant examples of Italian company town. Since the 80s, due to labor market crisis and to new geographies of production, the neighborhood is characterized by a divestment process of the activities that had generated it. It is also characterized by a gradual abandonment of the living space and by a relentless process of physical, cultural and social degradation. At Mirafiori however, as in other places, was decided to preserve and enhance the urban fabric, typical of the Fordist model but still recognized as urban, for its intrinsic and shared (by the public as by inhabitants) value. Since the ’90s, in fact, different urban regeneration projects followed to give a new image to the working-class neighborhood but, despite the huge amount of resources and expertise, they have always reached rather modest outcomes. On the other hand, the slowly and silently project, carried out by the local community, has started a process of taking into care and revival this part of the city that symbolically turned his back to the Factory to look out toward his river (Sangone) and be able to imagine a different future. Today the biggest challenge is to figure out if the place of affirmation of a right (housing for all) which ceased to be such, may contain new values, able to award a different identity.